2018
DOI: 10.1111/jth.13994
|View full text |Cite
|
Sign up to set email alerts
|

Age‐adjusted D‐dimer cut‐off leads to more efficient diagnosis of venous thromboembolism in the emergency department: a comparison of four assays

Abstract: Background The study compares different D-dimer assays and age-adjusted cut-offs in outpatients with suspected venous thromboembolism (VTE). The plasma concentration of this sensitive biomarker is increased by activated coagulation, but also by several conditions that are linked to an increased risk of VTE. One such condition is old age, which poses a common clinical problem where many prefer not to analyze D-dimer in elderly patients. Age-adjusted cut-offs have been validated for both deep venous thrombosis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 40 publications
1
34
0
5
Order By: Relevance
“…Another contemporary study by Farm et al investigated ageadjusted D-dimer for four different D-dimer assays and found the use of age-adjusted D-dimer approach improved specificity with maintained sensitivity in all four assays with a substantial decrease in false positives, similar to our study. 13…”
Section: Resultsmentioning
confidence: 99%
“…Another contemporary study by Farm et al investigated ageadjusted D-dimer for four different D-dimer assays and found the use of age-adjusted D-dimer approach improved specificity with maintained sensitivity in all four assays with a substantial decrease in false positives, similar to our study. 13…”
Section: Resultsmentioning
confidence: 99%
“…However, the D-dimer level increases with age and elderly patients are more prone to false-positive test results, which reduces the speci city of detection in these patients; therefore, studies have demonstrated the need to set the best cut-off value according to age to increase the speci city of detection [24] . In addition, any increased brin or decomposition process, such as pregnancy, cancer, trauma, in ammation, infection, etc., will increase the D-dimer level; therefore, an increase in the D-dimer level cannot be used for the speci c detection of VTE [25] . The D-dimer level alone is often unreliable for the diagnosis of DVT; however, as a low-cost and readily available biomarker, an elevated D-dimer level is useful for clinicians to identify or exclude VTE in patients based on symptoms and imaging ndings [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Samples were taken from the Karolinska Age Adjusted D-Dimer study (DFW-VTE). 5 In short, 954 consecutive outpatients with clinically suspected pulmonary embolism (PE) or deep venous thrombosis (DVT) in the lower limb were prospectively recruited from the emergency department of Karolinska University Hospital in Huddinge, Sweden, between April 2014 and May 2015. Medical students were separately enrolled as healthy controls for post hoc analysis.…”
Section: Patientsmentioning
confidence: 99%
“…4 The specificity of D-dimer is low at the chosen cutoff, with false positive results in up to 30% of tested patients with suspected VTE. 5 The low specificity is partially due to increased levels in patients with comorbidities. 6 Increasing the effectiveness of the diagnostic process could potentially have major clinical and economical beneficial effects on the management of VTE.…”
Section: Introductionmentioning
confidence: 99%